2017
DOI: 10.1002/app.44997
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐sensor fabrication by a layer‐by‐layer technique using polydiacetylene

Abstract: In order to increase the sensitivity of a polydiacetylene (PDA) sensor, PDA, and poly(sodium 4‐styrene‐sulfonate) (PSS) were alternately stacked to form a layer‐by‐layer (LBL) film on the quartz. In this study, N‐(2‐aminoethyl)pentacosa‐10,12‐diynamide (AEPCDA) was used as a constituent of the PDA and n‐butylamine was used as a target compound. The formed‐film sensor showed higher sensitivity than the vesicle solution. There was a large difference in sensitivity depending on the method used to form the LBL fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Therefore, almost reported PDA systems have been conducted in water. Our previous studies on PDAs were also conducted with a vesicle system in water . During the time we designed the PDA studies, we had difficulty because the target compounds were not soluble in water.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, almost reported PDA systems have been conducted in water. Our previous studies on PDAs were also conducted with a vesicle system in water . During the time we designed the PDA studies, we had difficulty because the target compounds were not soluble in water.…”
Section: Introductionmentioning
confidence: 99%
“…Polydiacetylene (PDA) vesicle is formed by the sonication of an amphiphilic diacetylene compound, following ultraviolet (UV) irradiation. The polymerized vesicles formed in this way are generally blue and change to red when a stimulus is applied . The stimuli for example, thermal, Pb 2+ , hydrocarbon, casein, mechanical force, warfare gas, Zn 2+ , salmonella, water, virus, organic acid, albumin, bacteria, and prostate cancer have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of liquid-type additives such as PFA, HMDS, or MWCNT/PFA hybrid additives for the improvement of the sound absorption properties of flexible PUF have not yet been reported. Recent studies of PUF with MWCNT composites [5,27] suggested that a small amount of MWCNTs in the polyurethane matrix may yield copious bubble nucleation by reducing the critical activation energy for nucleation. As a result, the MWCNT particles effectively reduced the cell size of the PUF, decreasing the thermal conductivity of the PUF.…”
Section: Introductionmentioning
confidence: 99%